Respuesta :

Answer:

10

Step-by-step explanation:

sqrt(9x+10) = x

Square each side

(sqrt(9x+10))^2 = x^2

9x+10 = x^2

Subtract 9x from each side

9x-9x+10 = x^2-9x

10 = x^2 -9x

Subtract 10 from each side

10-10 = x^2 -9x -10

0 = x^2 -9x -10

Factor

0 = (x-10) (x+1)

x =10, x=-1

Since we squared each side we need to check for extraneous solutions

sqrt(9x+10) = x

Let x = -1

sqrt(9(-1)+10) = -1

sqrt(-9+10) = -1

sqrt(1) = -1

1 = -1

False

Extraneous solution

sqrt(9x+10) = x

Let x = 10

sqrt(9(10)+10) = 10

sqrt(90+10) = 10

sqrt(10) = 10

True